Análise e comparação dos índices de eficiência física em partidas oficiais de futebol - VIEIRA, José Guilherme Bottentuit (2022)
Introduction: Soccer is a predominantly aerobic sport with intermittent characteristics. Physical trainers and physiologists have used external and internal load to develop different strategies to control training load. As a form of control, the ratio between external and internal load has been used in sports, called the physical efficiency index, being calculated by the formula (Distance per minute / %HRmax). Recently, it has been proposed to consider not the HR and the average speed, but also the accelerations performed due to the increase of these actions in football matches. In this way they propose a new IEF, through the formula ((Number of accelerations x Distance per minute)/%HRmax). Objective: To compare the efficiency index and the new efficiency index proposed in the literature in soccer matches. Materials and methods: The study analyzed 14 official matches, played by a professional soccer team of the B series in Brazil, composed of 11 athletes (age: 25.40 ± 3.24 years; weight: 74.17 ± 4.60 kg; height: 179.10 ± 7.94 cm; %F: 10.48 ± 1.14; %mm: 47.17 ± 1.67; IRL2: 696.00 ± 155.72 m; VO2: 54.76 ± 12.24 ml/Kg/min.), which maintained regular and systematic training, and competed in regional and national competitions organized by the Brazilian Football Confederation during the 2018 season. The variables analyzed were total distance covered, distance covered per minute, distance covered in speed zones, sprints, number of accelerations, number of decelerations and the calculation of the efficiency index was performed. Results: The mean values for the total distance covered marker were 9712.00 ± 490.90 m. The average values for the high-speed running marker were 496.80 ± 88.28 m. The distance covered in sprints was 173.98 ± 40.20m. The mean values for the number of accelerations were 103.4 ± 8.91. The mean values for the number of decelerations were 99.72 ± 9.06. When comparing the Efficiency Ratio and the New Efficiency Ratio, the New Efficiency Ratio was higher (Efficiency Ratio: 1.18; new Efficiency Ratio: 1.35; p < 0.05) in addition to a correlation moderate among them (r = 0.45). Conclusion: The present study verified that the new efficiency index, including the accelerations, presents itself as a more adequate tool in load control, because from the biomechanical and physiological point of view, it is a more demanding action, which generates high rates of development. of strength resulting in greater muscle damage leading to physiological and mechanical stress levels that can affect match performance and the post-match recovery schedule.